2021
DOI: 10.3171/2021.5.focus21212
|View full text |Cite
|
Sign up to set email alerts
|

Randomized study comparing 3D virtual reality and conventional 2D on-screen teaching of cerebrovascular anatomy

Abstract: OBJECTIVE Performing aneurysmal clipping requires years of training to successfully understand the 3D neurovascular anatomy. This training has traditionally been obtained by learning through observation. Currently, with fewer operative aneurysm clippings, stricter work-hour regulations, and increased patient safety concerns, novel teaching methods are required for young neurosurgeons. Virtual-reality (VR) models offer the opportunity to either train a specific surgical skill or prepare for an individual surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Despite the diversification of virtual simulators/platforms/systems used in undergraduate medical education, we found that 48 (52%) studies ( 18 , 22 , 23 , 27 31 , 33 35 , 37 39 , 42 , 44 48 , 50 , 52 , 54 , 57 67 , 71 , 72 , 75 , 78 , 81 84 , 93 , 96 , 99 , 101 , 103 , 105 ) reported the immersive VR application, which is characterized by the use of VR equipment consisting of head-mounted displays (headsets or goggles) and/or hand controllers. This finding suggested that VR might be a typical and popular representative of modern VS technology used in medical education.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Despite the diversification of virtual simulators/platforms/systems used in undergraduate medical education, we found that 48 (52%) studies ( 18 , 22 , 23 , 27 31 , 33 35 , 37 39 , 42 , 44 48 , 50 , 52 , 54 , 57 67 , 71 , 72 , 75 , 78 , 81 84 , 93 , 96 , 99 , 101 , 103 , 105 ) reported the immersive VR application, which is characterized by the use of VR equipment consisting of head-mounted displays (headsets or goggles) and/or hand controllers. This finding suggested that VR might be a typical and popular representative of modern VS technology used in medical education.…”
Section: Resultsmentioning
confidence: 87%
“…This finding suggested that VR might be a typical and popular representative of modern VS technology used in medical education. Moreover, only one third of (31) articles ( 15 , 16 , 22 , 26 , 31 33 , 38 , 47 , 48 , 52 , 53 , 56 , 58 , 60 – 62 , 64 , 65 , 67 , 71 , 73 , 75 , 76 , 78 80 , 95 , 96 , 101 , 105 ) included in this review were based on the commercially available or free VS softwares/platforms, the rest used the self-developed ones.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to preexisting virtual reality software programs, our software has a greater emphasis on anatomy as it relates to imaging and focuses on diagnosis rather than on anatomy visualization for treatment alone [ 8 , 10 , 11 ]. Additionally, unlike most surgical-focused virtual reality studies [ 24 ], our study includes both normal virtual angiography for educational intervention and normal CT angiography exams for assessment as well as virtual aneurysms and CT angiography with aneurysms. The presence of normal exams is more relevant for radiologists who interact with normal exams far more often than aneurysms and need to understand normal anatomy to correctly diagnose pathologic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…21 VR platforms facilitate the learning and understanding of the brain's spatial anatomy, and this is the preferred method compared with 2D images. 22,23 Furthermore, some studies have shown that neurosurgical simulation with photographic 3D models is a helpful, enjoyable, and attractive learning tool for neurosurgery residents and that further development of resources can aid the education of neurosurgeons. 14,[24][25][26] Initially, VR was found to accelerate the learning curve of novices, but more traditional and supervised training was required later on.…”
Section: Discussionmentioning
confidence: 99%